2006
DOI: 10.1590/s1807-59322006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of S-100b for Risk Classification of Victims Sustaining Minor Head Injury - First Pilot Study in Brazil

Abstract: Poli de Figueiredo LF, Biberthaler P, Simao Filho C, Hauser C, Mutschler W, Jochum M. Measurement of S-100B for risk classification of victims sustaining minor head injury -first pilot study in Brazil. Clinics. 2006;61(1):41-6.BACKGROUND: Release of the neuronal protein S-100B into the circulation has been suggested as a specific indication of neuronal damage. The hypothesis that S-100B is a useful and cost-effective screening tool for the management of minor head injuries was tested. METHODS: Fifty consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
1
39
0
1
Order By: Relevance
“…The design and patient characteristics of the 12 studies 98,113,115,130,[143][144][145][146][147][148][149][150] that evaluated the diagnostic accuracy of various biochemical markers for diagnosing ICI (including the need for neurosurgery) in adults and children with MHI are summarised in Table 18. Nine studies provided diagnostic data on protein S100B only, 98,113,115,[143][144][145][146][147][148][149] one on NSE only 115,130 and one on other markers [creatine kinase isozyme (CK-BB), noradrenaline, adrenaline, dopamine, amylase and total catecholamines].…”
Section: Description Of Included Studies (Design and Patient Charactementioning
confidence: 99%
See 1 more Smart Citation
“…The design and patient characteristics of the 12 studies 98,113,115,130,[143][144][145][146][147][148][149][150] that evaluated the diagnostic accuracy of various biochemical markers for diagnosing ICI (including the need for neurosurgery) in adults and children with MHI are summarised in Table 18. Nine studies provided diagnostic data on protein S100B only, 98,113,115,[143][144][145][146][147][148][149] one on NSE only 115,130 and one on other markers [creatine kinase isozyme (CK-BB), noradrenaline, adrenaline, dopamine, amylase and total catecholamines].…”
Section: Description Of Included Studies (Design and Patient Charactementioning
confidence: 99%
“…Nine studies provided diagnostic data on protein S100B only, 98,113,115,[143][144][145][146][147][148][149] one on NSE only 115,130 and one on other markers [creatine kinase isozyme (CK-BB), noradrenaline, adrenaline, dopamine, amylase and total catecholamines]. 150 One study 115 provided diagnostic data on both protein S100B and NSE levels.…”
Section: Description Of Included Studies (Design and Patient Charactementioning
confidence: 99%
“…Most of these studies have been conducted in adult and paediatric patients who had suffered head trauma of varying degrees. [4][5][6][7][8][9] Other studies ABSTRACT: Background: It has been shown previously that S-100β levels in serum correspond with the severity of central nervous system (CNS) trauma. It also has been suggested that S-100β in CNS tissue is involved in neuroprotection and neuroregeneration.…”
mentioning
confidence: 99%
“…Previous studies identified maximum sensitivity for abnormal head CT at an S100B level of 0.10-0.12 lg/L. 9,10,[25][26][27][28][29] In our cohort, the 98% sensitivity level was not reached until the S100B level was below 0.060 lg/L. At a cutoff of 0.10 lg/L, the FIG.…”
Section: Discussionmentioning
confidence: 68%